Factors Associated with the Occurrence of Pneumonia in Children Under Five in Tarus, Central Kupang, East Nusa Tenggara - Bendelina Rafael; Petrus Romeo; Enjelita M Ndoen (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Pneumonia is an acute infection that attacks the lung tissue (alveoli) caused by various microorganisms such as viruses, fungi and bacteria. The risk factors for pneumonia are environmental factors, individual child factors, and behavioral factors. Environmental factors include indoor air pollution, physical condition of the house, and residential density. Individual child factors include age, gender, nutritional status, low birth weight, immunization and breastfeeding. Behavioral factors include smoking habits, habit of opening and closing windows, and habit of cleaning the house. The study aimed to analyze the factors associated with the incidence of pneumonia in children under five in Tarus Village, Central Kupang, East Nusa Tenggara. Subjects and Method: An analytic survey study with a cross-sectional design was conducted in the Tarus Village, Kupang Tengah, Kupang, East Nusa Tenggara from August to September 2022. A total of 88 mothers of children under five aged 12-59 months in the Tarus Village, Kupang Tengah District, Kupang Regency, East Nusa Tenggara were selected for this study. The dependent variable is the incidence of pneumonia in children under five. The independent variables are the type of floor, lighting, ventilation, occupancy density, smoking habit, habit of opening windows, and habit of cleaning the house. Data were collected using a questionnaire and analyzed using the chi-square test. Results: There is a relationship between house ventilation (OR= 5.83; 95% CI= 1.05 to 1.34; p= 0.003), house floor (OR= 4.65; 95% CI= 1.57 to 1.77; p= 0.001), house lighting (OR= 6.22; 95% CI= 1.09 to 1.25; p= 0.005), occupancy density (OR= 6.90; 95% CI=1.18 to 1.37; p= 0.001), window opening behavior (OR= 5.34; 95% CI= 1.26 to 1.46; p = 0.004), and house cleanliness (OR= 8.55; 95% CI= 1.07 to 1.22; p= 0.002) on the incidence of pneumonia. Conclusion: House ventilation, house floors, lighting, occupancy density, window opening behavior, and house cleanliness are significantly related to the incidence of pneumonia. Keywords: pneumonia, risk factors, children under five. Correspondence: Bendelina Rafael. Study Program of Public Health, Faculty of Public Health, Universitas Nusa Cendana. Lasiana, Klp. Lima, Kupang, East Nusa Tenggara. Email: ellarafael780@gmail.com. Mobile: +6282123890312.